Sztuka jako przestrzeń konfliktu. Istota, kreowanie i upowszechnianie jako obszary zmagań tożsamościowych - Klimek, Jordan (Kultura-Społeczeństwo-Edukacja, 2024)
The text analyzes the reality of art as a space filled with contradictions. The critical literature analysis covers three perspectives: the essence, creation, and dissemination of art. The conclusions point to the necessity of openly defining art as a social construct, as well as to conflictual situations such as the quality of relations within the art community, competition for position in the environment and the art market, social expectations of the role of artists in the modern world, the rupture of continuity of meaning within language and cultural heritage, relations with the external environment, or the determinants of access to economic capital. At the same time, art demonstrates the potential for discourse leading to bold questions, the search for answers and the “clash” of different perspectives on the place and role of man in current reality.